2022
DOI: 10.1039/d2ee00722c
|View full text |Cite|
|
Sign up to set email alerts
|

Low-cost solutions to global warming, air pollution, and energy insecurity for 145 countries

Abstract: Timeline to transition 145 countries to 100% wind-water-solar by 2035, with 80% by 2030.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…[62] is the most cited article in the field, and it has helped to overcome belief systems and barriers across different fields on a global scale, and to catalyze a global breakthrough of 100% RE. Updated research by Jacobson et al [13], [65], [66], [67], [68], [69] has overcome the previously identified limitations, and has provided more detailed energy system results for almost all countries in the world, as well as grid analyses of 20 or 24 representative regions encompassing the countries. The first study examining specifically 100% renewable transportation was published in 2005 [70].…”
Section: Milestones In the History Of 100% Renewable Energy Systems A...mentioning
confidence: 99%
See 4 more Smart Citations
“…[62] is the most cited article in the field, and it has helped to overcome belief systems and barriers across different fields on a global scale, and to catalyze a global breakthrough of 100% RE. Updated research by Jacobson et al [13], [65], [66], [67], [68], [69] has overcome the previously identified limitations, and has provided more detailed energy system results for almost all countries in the world, as well as grid analyses of 20 or 24 representative regions encompassing the countries. The first study examining specifically 100% renewable transportation was published in 2005 [70].…”
Section: Milestones In the History Of 100% Renewable Energy Systems A...mentioning
confidence: 99%
“…Most global models subdivide the world into 12-24 regions as shown in Table 1, which limits their ability to analyze important details. The studies of Jacobson et al [66], [13], [69] performed annual-average 100% RE analyses for 139, 143, or 145 countries, then grouped those countries into 20 or 24 world regions, respectively, for grid analyses at a time resolution of 30 seconds for multiple years. Countries were grouped for grid analyses because currently, many countries are interconnected, and interconnecting reduces costs relative to isolating countries [68].…”
Section: A Global 100% Renewable Energy System Studies and Models Usedmentioning
confidence: 99%
See 3 more Smart Citations